Euclidean Distance Transform (EDT) Algorithm Applied to Binary Image for Finding Breast Cancer - Angayarkanni, N.; Kumar, D. (Biomedical & pharmacology journal, 2015)
Breast Cancer is a serious and common disease that affects thousands of women every year in the World. Early Detection of Breast Cancer is critical for effective treatment. Mammogram is the seed stage for Mammography and Early Detection of Breast Cancer with correct screening save lives of millions of peoples in the World. Breast Cancer that Originates from inner lining of Milk ducts. Currently we have studied the location, Tissue background and Image Characteristic of Breast Cancer in three phase. First Phase we worked on converting the Gray scale image in to Binary image and in the Second Phase we described the work done for omitting the image which is having only the dark content by the usage of pixel brightness. In this paper we are described about Euclidean Distance Transformation through Image Triangulation. The results indicate that the importance of effectively displaying information in the lighter areas of the Mammogram with sufficient contrast of Mammogram Image. This approach is clearly gives the easy way to obtain the area of cancer in a breast during the screening.